Exploring human resources, marketing and promotion activities towards the sustainable tourism development in Phu Quoc islands, Vietnam - Hieu, Vu Minh; Vu, Ngo Minh; Nwachukwu, Chijioke (Zielona Góra: Faculty of Economics and Management Press)
Phu Quoc island of Kien Giang Province in Vietnam is endowed with resources for tourism development. The study explored the human resources, tourism marketing and promotion efforts of businesses towards the sustainable tourism development in Phu Quoc tourism. The authors used secondary and primary data to elicit information from respondents. Secondary data was collected from Kien Giang department of tourism, Statistical departments of Kien Giang and Phu Quoc.
Keywords: tourism development; human resources; ourism marketing; promotion; Vietnam; rozwój turystyki; zasoby ludzkie; marketing turystyczny; promocja; Wietnam